2013
DOI: 10.1107/s1399004713025030
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of new deoxycytidine kinase inhibitors rationalizes the affinity-determining moieties of the molecules

Abstract: Deoxycytidine kinase (dCK) is a key enzyme in the nucleoside salvage pathway that is also required for the activation of several anticancer and antiviral nucleoside analog prodrugs. Additionally, dCK has been implicated in immune disorders and has been found to be overexpressed in several cancers. To allow the probing and modulation of dCK activity, a new class of small-molecule inhibitors of the enzyme were developed. Here, the structural characterization of four of these inhibitors in complex with human dCK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Moreover, dCK provides an escape mechanism when DNA de novo synthesis is inhibited by ribonucleotide reductase inhibitors (6). This resistance can be overcome using small-molecule inhibitors of dCK (6)(7)(8)(9). dCK is also required to phosphorylate and activate inactive prodrugs such as cytarabine, gemcitabine, decitabine, and cladribine (10).…”
mentioning
confidence: 99%
“…Moreover, dCK provides an escape mechanism when DNA de novo synthesis is inhibited by ribonucleotide reductase inhibitors (6). This resistance can be overcome using small-molecule inhibitors of dCK (6)(7)(8)(9). dCK is also required to phosphorylate and activate inactive prodrugs such as cytarabine, gemcitabine, decitabine, and cladribine (10).…”
mentioning
confidence: 99%
“…Additionally, for each ligand-bound structure, a supplementary electron density was present at the top of the cavity (Supplementary Fig. 11 ), likely corresponding to a second molecule of compound interacting weakly with the first one in a similar binding mode as the ‘F-series’ inhibitors reported previously 38 . Moreover, it should be noted that masitinib and imatinib were able to open dCK in situ, since we were able to obtain these 3D structures in the ‘open’ conformation by soaking the protein kinase inhibitors in a ‘closed’ dCK crystal.…”
Section: Resultsmentioning
confidence: 65%
“…In contrast, the tighter binding propyl-containing molecules were observed to bind with a single inhibitor molecule, at position 1, per dCK active site. 9 This revealed that binding of two molecules is not required for high affinity. In our previous report, we analyzed the implication of single versus double binding of inhibitor molecules to dCK and concluded that inhibition of dCK is primarily caused by the binding of the inhibitor at position 1, whereas the molecule bound at position 2 does not appreciably enhance the inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work we demonstrated that the nature of the substituent at the thiazole ring 5-position (part C of the molecule, Figure 1 A) plays a crucial role in binding affinity. 9 In short, we compared having no substituent at that position to having a methyl, ethyl, or propyl. We found that propyl dramatically improved the binding affinity, and as a result, compounds with a propyl at the 5-position became our lead compounds (i.e., compounds 1 and 2 , Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation